Digital transformation, strategic resilience, cyber security and risk management - Grima, Simon; Thalassinos, Eleftherios; Noja, Gratiela Georgiana; Stamataopoulos, Theodore V.; Vasiljeva, Tatjana; Volkova, Tatjana (Contemporary studies in economic and financial analysis ;, 2023)
Digitization of economic and management processes allows for the delivery of new value and higher efficiency in the implementation of strategic goals. This is due to the inclusion of digital technologies in the existing rules of functioning among partners involved in the flow of resources, and from their readiness for digital transformation. A significant challenge, in practical, organizational, and scientific terms is to understand the opportunities and threats resulting from digital transformation, to identify optimal strategies for the development of business entities in new economic and management conditions, taking care to adopt collateral and proper management of new risks. Addressing this challenge to the readers - contributors indicate the latest theoretical advances, and practical examples in FinTech, The Internet of Things, and AI, among others. This results in a synthetic look at the complex digital transformation processes of the modern world, both in terms of the underlying causes and the vast effects of the transformations and digitization of social and economic life. Contemporary Studies in Economic and Financial Analysis publishes a series of current and relevant themed volumes within the fields of economics and finance.